Gas-to-power in North Africa: Implications for gas exports and supply - Darbouche, H (Oxford Institute for Energy Studies, 2010)
The power sector in North African gas exporters Algeria, Egypt and Libya, as well as in transit countries Tunisia and Morocco, has been the main driver of growth in gas consumption since the introduction of the fuel in the respective energy balances of these countries. With demand for electricity expected to show no signs of abating in the medium term, the exporting countries are facing added pressure on their gas export expansion plans, while Morocco and to a lesser extent Tunisia are having to make tough decisions with regard to future gas supply options. Issues of artificially low domestic prices, endemic to the gas-and-power sector across the region, lie at the heart of these challenges.